Corticosteroids and pulmonary rehabilitation reducing long‐term morbidity in a patient with post‐COVID‐19 pneumonitis: A case study. (13th March 2021) - Fanshawe, Jack; Howell, Jack; Omar, Adhnan; Piper, Megan; Simpson, Thomas
Abstract: Background: Whilst research efforts have focussed on treatment during the acute phase, little work has focussed on the long‐term sequelae of COVID‐19 infection. This case described a patient who remained symptomatic several weeks after discharge from hospital with what was diagnosed as a COVID‐19 infection. There were significant deficits shown in his functional exercise testing, his pulmonary functions testing and there was evidence of fibrotic changes on his radiology. Methods: As part of a multidisciplinary clinic, he was started on steroids and a tailored pulmonary rehabilitation course over a course of 6–8 weeks. Thereafter, his exercise testing, pulmonary function tests and radiology were all repeated to see progress. Results: On completing the course of corticosteroids and concurrent personalised pulmonary rehabilitation, there was a dramatic improvement in the patient's symptom severity, radiology and pulmonary function. The most significant improvement noted was in his exercise testing, namely a 6‐min walk test and 1 min of sit‐to‐stands. Before treatment, he had a Medical Reserch Council (MRC) score of 2, and after it returned to his baseline of 0. Discussion: Using corticosteroids and exercise training that allowed quantitative evaluation throughout the stages of recovery was a valuable tool to gauge progress and response to treatment. These therapies present opportunity to prevent the development of irreversible pulmonary fibrosis that could prove to be a major breakthrough in reducing long‐term morbidity and improving the quality of life of those affected.